Microstructured capacitive sensor with broad detection range and long-term stability for human activity detection - Xin He (Nature Portfolio, 2021)
Abstract In recent years, flexible stress sensors capable of monitoring diverse body movements and physiological signals have been attracting great attention in the fields of healthcare systems, human–machine interfaces, and wearable electronics. Inspired by the structure of natural eggshell inner membrane (ESIM), we developed a pressure sensor based on MXene (Ti3C2Tx)/Ag NWs (silver nanowires) composite electrodes and the micro-structured dielectric layer to meet the application requirements of wide detection range and long-term stability for the sensors. In the light of the nanoscale-microarray of the dielectric layer and the rough surface of electrode materials, this pressure sensor is expected to allow great and persistent deformation during the loading process. As a result, the device is characterized by an improved sensitivity, fast response (in the millisecond range), wide detection range (0–600 kPa), and long-term stability. The outstanding performance of the proposed sensor makes it possible to detect various human activities, such as speaking, air blowing, clenching, walking, finger/knee/elbow bending, and striking, demonstrating its good application prospects in wearable and flexible electronic devices.